Electrochemotherapy in the treatment of metastatic malignant melanoma: a prospective cohort study by InspECT. (26th April 2017) - Kunte, C.; Letulé, V.; Gehl, J.; Dahlstroem, K.; Curatolo, P.; Rotunno, R.; Muir, T.; Occhini, A.; Bertino, G.; Powell, B.; Saxinger, W.; Lechner, G.; et al.
Summary: Background: (ECT) is an effective local treatment for cutaneous metastasis. Treatment involves the administration of chemotherapeutic drugs followed by delivery of electrical pulses to the tumour. Objectives: To investigate the effectiveness of ECT in cutaneous metastases of melanoma and to identify factors that affect (beneficially or adversely) the outcome. Methods: Thirteen cancer centres in the International Network for Sharing Practices on Electrochemotherapy consecutively and prospectively uploaded data to a common database. ECT consisted of intratumoral or intravenous injection of bleomycin, followed by application of electric pulses under local or general anaesthesia. Results: In total, 151 patients with metastatic melanoma were identified from the database, 114 of whom had follow‐up data of 60 days or more. Eighty‐four of these patients (74%) experienced an overall response (OR = complete response + partial response). Overall, 394 lesions were treated, of which 306 (78%) showed OR, with 229 showing complete response (58%). In multivariate analysis, factors positively associated with overall response were coverage of deep margins, absence of visceral metastases, presence of lymphoedema and treatment of nonirradiated areas. Factors significantly associated with complete response to ECT treatment were coverage of deep margins, previous irradiation of the treated area and tumour size (< 3 cm). One‐year overall survival in this cohort of patients was 67% (95% confidence interval 57–77%), while melanoma‐specific survival was 74% (95% confidence interval 64–84%). No serious adverse events were reported, and the treatment was in general very well tolerated. Conclusions: ECT is a highly effective local treatment for melanoma metastases in the skin, with no severe adverse effects noted in this study. In the presence of certain clinical factors, ECT may be considered for local tumour control as an alternative to established local treatments, or as an adjunct to systemic treatments. Abstract : What's already known about this topic? Electrochemotherapy (ECT) is an effective local treatment for cutaneous metastasis. Treatment efficacy is correlated to tumour size. What does this study add? With multivariate analysis, several new factors associated with a favourable response to treatment have been identified: coverage of deep tumour margin, presence of lymphoedema, treatment of nonirradiated areas and absence of visceral metastases. Respond to this article Linked Comment:Cerio and Moir. Br J Dermatol 2017; 176:1427